Aggregate Boid behavior to aid in artificial autopoietic organization - Steven Lawrence; Chrystopher L. Nehaniv (BioSystems, 2024)

EEG-Meta-Microstates: Towards a More Objective Use of Resting-State EEG Microstate Findings Across Studies - Thomas Koenig; Sarah Diezig; Sahana Nagabhushan Kalburgi; Elena Antonova; Fiorenzo Artoni; Lucie Brechet; Juliane Britz; Pierpaolo Croce; Anna Custo; Alena Damborská; Camila Deolindo; Markus Heinrichs; et al. (Brain Topography, 2024)
Over the last decade, EEG resting-state microstate analysis has evolved from a niche existence to a widely used and well-accepted methodology. The rapidly increasing body of empirical findings started to yield overarching patterns of associations of biological and psychological states and traits with specific microstate classes. However, currently, this cross-referencing among apparently similar microstate classes of different studies is typically done by “eyeballing” of printed template maps by the individual authors, lacking a systematic procedure. To improve the reliability and validity of future findings, we present a tool to systematically collect the actual data of template maps from as many published studies as possible and present them in their entirety as a matrix of spatial similarity. The tool also allows importing novel template maps and systematically extracting the findings associated with specific microstate maps from ongoing or published studies. The tool also allows importing novel template maps and systematically extracting the findings associated with specific microstate maps in the literature. The analysis of 40 included sets of template maps indicated that: (i) there is a high degree of similarity of template maps across studies, (ii) similar template maps were associated with converging empirical findings, and (iii) representative meta-microstates can be extracted from the individual studies. We hope that this tool will be useful in coming to a more comprehensive, objective, and overarching representation of microstate findings.

Autopoiesis: Foundations of life, cognition, and emergence of self/other - Pasquale Stano; Chrystopher Nehaniv; Takashi Ikegami; Luisa Damiano; Olaf Witkowski (BioSystems, 2023)

Perception–action loops of multiple agents: informational aspects and the impact of coordination - Philippe Capdepuy; Daniel Polani; Chrystopher L. Nehaniv (Theory in Biosciences, 2012)